Campaigning to close the pay gap - badge 2000 (2000)
2000 1960-2000 "Campaigning to close the pay gap - badge 2000" [EP0141], 2000 This badge was issued as part of celebrations to mark the 30th anniversary of the Equal Pay Act at Congress House in June 2000. The event was attended by successful equal pay applicants and others, including Barbara Castle. The badge was later adapted and used as the 2000 TUC Congress badge.